The Role of the Incontinence Severity Index in the Treatment of Stress Urinary Incontinence - Bilgin Öztürk; Ufuk Atlıhan (Journal of Urological Surgery)
Objective: To evaluate the effects of medical and surgical treatment of stress urinary incontinence (SUI) on incontinence severity index (ISI). Materials and Methods: In our study, 64 patients aged 30-60 years, who were admitted to our hospital with symptoms of SUI between 2018 and 2023, underwent medical or surgical treatment for SUI, and met the inclusion criteria, were included. Women included in the study were divided into three groups: those who received medical treatment, those who underwent Burch colposuspension, and those who received tension-free obturator tape (TOT). Results: When ISI measurements were categorized between the groups in the pre-treatment period, it was found that the rate of patients with slight and moderate SUI was significantly higher in the medical treatment group (p=0.018 and p=0.044, respectively). The rate of patients with severe SUI was found to be significantly lower in the medical treatment group (p=0.032). When the groups were evaluated individually, the post-treatment ISI score was found to be significantly lower than the pre-treatment ISI score in all groups (p<0.001). The difference between pre-treatment and post-treatment ISI scores (ΔISI) was found to be significantly higher in the TOT group and Burch colposuspension group compared to the medical treatment group (p<0.001). Conclusion: ISI is useful in assessing the severity of incontinence in patients with SUI and the effectiveness of treatment after treatment. For ISI to be widely used as an alternative, prospective use with a larger number of patients and longer follow-up periods is needed.